Pengaruh Kerjasama Tim dan Pengawasan terhadap Kinerja Pegawai Pada Perumda Air Minum Wair Pu’an Kabupaten Sikka: (Studi Kasus Pada Kinerja Pegawai Pada Perumda Air Minum Wair Pu’an Kabupaten Sikka) - Willibrodus Kladius Gama; Magdalena Silawati Samosir; Yustina Olivia Da Silva (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
This Research aimed to (1) provide an overview of Employee Performance, Teamwork, and Supervisison; and (2) analayze the influence of Teamwork and Supervision on EmployeePerformance both partially and simultaneously. The research population consisted of 60 employees of Wair Puan Regional Water Supply Company in Sikka Regency. Using The Slovin formula, the sample size for this study was determined to be 37 employees. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, specifically multiple linear regression.Hypothesis testing was conducted through F-tests and t-tests. The descriptive analysis results indicated that the Employee Performance variable falls within good criteria, the Teamwork variable falls within low criteria, and the Supervision Variable falss within high criteria. The t-tests statistical results showed that, partially, the teamwork variable had a positive and significant effect on Employee Performance. Aditionally, the Supervision Variable also had a positive and significant effect on Employee Performance. The F-test results indicated that, simultaneously, the Teamwork and Supervision variables significantly influence Employee Performance. The coefficient of determination analysis showed that the two independent Variables in this Study explain 37.60% of the variation in Employee Performance at Wair Puan Regional Water Supply Company in Sikka Regency.